MEMAHAMI NARASI KOMUNIKASI TUBUH PEREMPUAN - Kusdwianti, Eviana; Dwiningtyas Sulistyani, Hapsari; Sunarto, Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Menstruation is a normal part of women’s body, so it should be discussed normally like any other topic. However, negative perspective, disgust, and certain norms make it difficult for women to express themselves and discuss their menstrual experiences. This study aims to un-derstand how menstruation as part of women’s body is communicated from the very first mens-truation until the last menstruation. Critical paradigm is used to reveal various inequalities, negative treatment, and the negative impacts experienced by women, by using muted group theory and communication privacy management theory. The data obtained from in-depth inter-views with seven informants are analyzed using the critical narrative study method. The results of this study revealed that menstruation is a topic that is avoided, and discussions about menstruation will only occur in urgent situation. Women experienced lot of difficulities because the lack of discussion about menstruation as a part of the body with pa-rents. This problem continues as time goes because discussions about menstruation are also avoided in the school—both with friends and educators—, in the doctor’s consult room, in the work environment, and also with partners. This brings negative impact such; alienation from one’s own body, difficulties in ex-pressing oneself, conflicts with partners, and losing the education rights, health rights, and al-so sanitation rights. The study also found that women received negative treatment during menstruation, starting from those closest to them; from both men and fellow women who also menstruate. However, women begin to accept this negative treatment as something normal and they also start to interpret their menstrual experiences based on man’s perspective.